All-Trans Retinoic Acid Reduces Matrix Metalloproteinase-2 and Increases E-Cadherin Levels in BeWo Choriocarcinoma Cells - Nurseta, Tatit; Harumsari, Stefani; Prasetya, Nanda Agus; Indrawan, I Wayan Agung (Bangladesh Journal of Medical Science, 2023)
Background: Choriocarcinoma is a malignant trophoblastic tumor that can degrade the uterine basement membrane to facilitate local and distant metastasis. Matrix metalloproteinase-2 (MMP-2) is a vital proteinase produced by trophoblasts and can cleave type IV collagen in the basement membrane of the uterine epithelium. In addition, E-cadherin controls cell adhesion, which is associated with tumorprogression, and loss of E-cadherin function is associated with metastasis. Vitamin A analogues, including all-trans retinoic acid (ATRA), exhibit anticancer properties, including metastasis inhibition.This study aimed to investigate the ability of ATRA to prevent trophoblast invasion and metastasis in choriocarcinoma by assessing MMP-2 and E-cadherin activity. Methods: This study administered various doses of ATRA to the BeWo (American Type Culture Collection CCL-98) choriocarcinoma cell line and assessed MMP-2 and E-cadherin activity through flow cytometry. The research was performed at the Biomedical Laboratory of the Faculty of Medicine of Universitas Brawijaya Malang, East Java, Indonesia. Results: BeWo cells were exposed to 0, 50, 100, 200, 400, or 800 μg/mL ATRA. MMP-2 was downregulated after ATRA treatment. The greatest reduction in MMP-2 level was observed after 200 μg/mL ATRA treatment, but this result was not statistically significant (P = 0.550). However, ATRA treatment significantly reduced the number of BeWo cells with low E-cadherin levels (P = 0.012). Conclusion: ATRA downregulates MMP-2 and upregulates E-cadherin. Further in vitro and animal studies are required to evaluate the ability of ATRA to inhibit metastasis. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 336-340